The South African Museum's Meiring Naude cruises, part 4: Echinoderms - Clark, A. M. (Ann. S. Afr. Mus., 1977)
This paper lists the echinoderm species recently collected in deep water off Natal and is annotated to indicate the eighteen new records for the South African area and resultant extensions of range. Notes are also given to distinguish the additional species from those keyed and described in a recent paper.